ROTRE a device for the control of rodent infestation in commercial kitchens - Atanacio, Andrea Marie M. (College of Fine Arts, University of the Philippines Diliman, 2017)
Rodent invasion is one of the problems faced in terms of maintenance and sanitation in commercial kitchens. It is necessary to further investigate and improve this service to avoid serious damages and the burden of commercial kitchens in dealing with these pests. With this, the concept of a device for rodent management in commercial kitchens was developed. Through this simple device can make a big difference in terms of ease and lessening the burden of dealing with this unruly pests in kitchens. With this in mind, ROTRE: rodent trap and repellent focuses on improving the sanitation and maintenance of commercial kitchens and lessen the burden for the people in preventing these pests from lurking through their kitchen premises.